INCREASING THE EFFICIENCY OF THE USE OF ARABLE LAND OF THE ALMATY REGION (ON THE EXAMPLE OF RAIYMBEK DISTRICT) (Journal of Geography and Environmental Management, 2020)
The article presents problems associated with enhancing the efficiency of arable land use in Raiymbek region of Almaty Oblast. The dynamics of changes in the area of agricultural land, including arable land, are shown based on statistical data for 2011-2018. As a result of the study, the main factors hindering the increase of soil fertility of arable lands and ways to prevent them were considered. The monitoring of rainfed and irrigated arable land was carried out in comparison with the statistical indicators of cultivated areas of rural regions. The number of land users and owners (private farms, jointstock companies, cooperatives and non-state enterprises) was also determined; the dynamics of arable land areas owned by them for 2013-2018 were shown. The analysis of the level of development of arable land identified the main reasons for the withdrawal of land from agricultural turnover. Moreover, the modern system of irrigation system development was studied; recommendations for monitoring and rational use of irrigated lands were developed. Priority areas of efficiency of arable land use, taking into account territorial features of the area, are defined. A map of the area’s agricultural land was developed using the GIS (ArcGIS) program.
Keywords: agricultural land, rainfed arable land, irrigated land, land monitoring, GIS.